EARLY DIAGNOSIS OF RHEUMATOID ARTHRITIS AND ITS IMPACT ON DISEASE PROGNOSIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Rheumatoid arthritis is a systemic, inflammatory, autoimmune disease that most commonly targets the synovial tissue of peripheral joints, leading to chronic pain, swelling, stiffness, and eventual destruction of cartilage and bone. This process, if unchecked, results in progressive joint deformity, disability, and a diminished quality of life. The importance of early diagnosis, as well as prompt and precise intervention, has become increasingly recognized over recent years as fundamental factors in improving disease outcomes and mitigating the long-term consequences of rheumatoid arthritis.